ANTIBACTERIAL ACTIVITY OF PAPUYU FISH SCALES CHITOSAN (Anabas testudineus) AGAINST Enterococcus faecalis - Ninda Andrea Haliza; Muhammad Yanuar Ichrom Nahzi; Alexander Sitepu; Nurdiana Dewi; Deby Kania Tri Putri (FKG ULM, 2025)
ABSTRACTBackground: Papuyu fish is widely consumed by Kalimantan people. Papuyu fish scales chitosan has antibacterial potential because it contains amino polysaccharides and enzyme lysozyme which inhibits the growth of root canal bacteria, specifically Enterococcus faecalis. Purpose: The purpose of this experimental is to analyze the antibacterial activity of papuyu fish (Anabas testudineus) scales chitosan against Enterococcus faecalis. Methods: This is a true experimental study with post-test only with a control group design using 15 samples of papuyu fish (Anabas testudineus) scales chitosan grouped into 5 treatment groups and 3 samples repetitions. The treatment groups consisted of papuyu fish (Anabas testudineus) scales chitosan concentrations of 25%, 50%, 75%, 100%, and distilled water (negative control). Absorbance calculation using a UV-Vis Spectrophotometer 722 for minimum inhibitory concentration (MIC) and Enterococcus faecalis colonies are visualized with a colony counter for minimum bactericidal concentration (MBC). Results: The MIC value of papuyu fish (Anabas testudineus) scales chitosan were obtained at 25% concentration and the MBC value were obtained at 100% concentration. The results of One-Way ANOVA test for MIC and Kruskal Wallis for MBC of papuyu fish scales chitosan concentrations of 25%, 50%, 75%, and 100% obtained significant results of p<0,05 and showed a significant difference between treatments. Conclusion: These are differences in the effectiveness of MIC and MBC papuyu fish (Anabas testudineus) scales chitosan concentrations of 25%, 50%, 75%, 100% and distilled water. Papuyu fish scales chitosan 100% concentration is the most effective concentration as an antibacterial against the growth of Enterococcus faecalis.